2021
DOI: 10.3389/fpsyg.2021.633663
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators in Adolescent Psychotherapy Initiated by Adults—Experiences That Differentiate Adolescents’ Trajectories Through Mental Health Care

Abstract: Mental health problems start early in life. However, the majority of adolescents fulfilling the criteria for mental health disorders do not receive treatment, and half of those who do get treatment drop out. This begs the question of what differentiates helpful from unhelpful treatment processes from the perspective of young clients. In this study, we interviewed 12 young people who entered mental health care reluctantly at the initiative of others before the age of 18. Their journeys through mental health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…They, therefore, used complementing strategies to obtain the prerequisite for client engagement – namely, the first meeting between therapist and client, thus, the starting point for the development of the therapeutic relationship. The therapists’ descriptions of their behaviors and strategies also are in line with recommendations for enhancing client engagement in adolescent clients ( Bolton Oetzel and Scherer, 2003 ) and show high degrees of sensitivity to known barriers to seeking and receiving mental health care among adolescents ( Radez et al, 2021 ; Stige et al, 2021 ). Yet, participants reported that their clinical priorities and preferred strategies for client engagement were under pressure.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…They, therefore, used complementing strategies to obtain the prerequisite for client engagement – namely, the first meeting between therapist and client, thus, the starting point for the development of the therapeutic relationship. The therapists’ descriptions of their behaviors and strategies also are in line with recommendations for enhancing client engagement in adolescent clients ( Bolton Oetzel and Scherer, 2003 ) and show high degrees of sensitivity to known barriers to seeking and receiving mental health care among adolescents ( Radez et al, 2021 ; Stige et al, 2021 ). Yet, participants reported that their clinical priorities and preferred strategies for client engagement were under pressure.…”
Section: Discussionmentioning
confidence: 66%
“…This study is part of a larger study on adolescent psychotherapy in which adults initiated the process without the adolescents initially wanting therapy, consisting of individual interviews with adolescent clients and focus group interviews with therapists. Previous publications from the project include an article presenting therapists’ conceptualization of adolescent clients coming to therapy at the initiative of others ( Barca et al, 2020 ), and one on adolescent clients’ experienced barriers and facilitators within different therapeutic trajectories ( Stige et al, 2021 ). Therapists were found to have partly diverging conceptualizations of adolescents coming reluctantly to treatment, represented by the themes: The hurt and distrustful adolescent; The adolescent lacking hope for the future; The adolescent engulfed in the burden of mental-health suffering; and The adolescent as something more than a psychiatric patient ( Barca et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations